A carbon based-screen-printed electrode amplified with two-dimensional reduced graphene/Fe3O4 nanocomposite as electroanalytical sensor for monitoring 4-aminophenol in environmental fluids. (May 2023) - Wang, Moxi; Feng, Li
Abstract: The analysis water pollutants are so important strategy for investigation of water quality. On the other hand, 4-aminophenol is known as a hazardous and high-risk compound for humans, and its detection and measurement is very important for investigating the quality of surface and groundwater. In this study, graphene/Fe3 O4 nanocomposite was synthesized by a simple chemical method and characterized by EDS and TEM methods and results showed Nano spherical shape of Fe3 O4 nanoparticle with diameter about 20 nM decorated at surface of 2D reduce graphene nanosheet (2D-rG-Fe3 O4 ). The 2D-rG-Fe3 O4 was used as excellent catalyst at surface of carbon-based screen-printed electrode (CSPE) and used as electroanalytical sensor in monitoring and determination of 4-aminophenol in waste water sample. The results confirmed improving ∼4.0 times in oxidation signal and reducing 120 mV in oxidation potential of 4-aminophenol at surface of 2D-rG-Fe3 O4 /CSPE compare to CSPE, respectively. The electrochemical investigation showed pH dependence behavior with equal value of electron and proton for -aminophenol at surface of 2D-rG-Fe3 O4 /CSPE. Using square wave voltammetry method (SWV), the 2D-rG-Fe3 O4 /CSPE successfully monitored 4-aminophenol in the concentration range 1.0 nM–200 μM. Finally, 2D-rG-Fe3 O4 /CSPE monitored 4-aminophenol in the different environmental fluids such as urban waste water, industrial waste water and river samples with recovery range 97.2%–104.3% that confirm powerful ability of 2D-rG-Fe3 O4 /CSPE as analytical tool. Graphical abstract: Image 1 Highlights: Introduce of reduced graphene/Fe3 O4 nanocomposite as a powerful electrocatalyst. Carbon based-screen-printed electrode amplified with reduced graphene/Fe3 O4 nanocomposite as a new electrochemical sensor. Electroanalytical sensor for monitoring 4-aminophenol in environmental fluids.